2013
DOI: 10.1108/jeim-05-2013-0024
|View full text |Cite
|
Sign up to set email alerts
|

Determinant factors of information communication technology (ICT) adoption by government‐owned universities in Nigeria

Abstract: PurposeThe purpose of this paper is to specifically investigate and prioritize the effects of 13 factors in determining ICT adoption in Nigerian universities.Design/methodology/approachThe constructs of theoretical framework of technology‐organization‐environment (T‐O‐E) underpin the survey. The survey adopted in‐depth unstructured and semi‐structured interviews with 30 senior executives drawn purposefully from at least one university in each of the five state capitals in south‐eastern Nigeria.FindingsEvidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 45 publications
1
77
0
Order By: Relevance
“…These include lack of appropriate support (Nneka, ). Addressing that issue is essential to the successful implementation of e‐training in Africa (Eze et al, ).…”
Section: E‐training Adoption In Africamentioning
confidence: 99%
See 2 more Smart Citations
“…These include lack of appropriate support (Nneka, ). Addressing that issue is essential to the successful implementation of e‐training in Africa (Eze et al, ).…”
Section: E‐training Adoption In Africamentioning
confidence: 99%
“…To improve this situation, the Nigerian government has endeavored to improve access to the technology needed to bring its civil service and, in particular, the quality of the training programs that it offers, up to date with that of other nations. The financial backing and management support needed to bolster these efforts to upgrade training, however, remain insufficient (Eze, Awa, Okoye, Emecheta, & Anazodo, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus organizations from developed economies have attained a significant level of adoption leaving their counter parts from developing countries far behind and still struggling with its implementation challenges. Researchers examining the adoption barriers from developing country perspectives such as Nigeria (Apulu & Latham, 2009;Apulu & Ige, 2011;Ibironke et al, 2011;Eze et al, 2013), India (Ahuja et al, 2009), Malaysia (Jafari et al, 2006;Mui et al, 2002), Egypt (Aboelmaged, 2014), Iran ( Sidawi et al, 2012), Brazil (Goedhuys & Veugelers, 2012), South Africa (Ogunyemi, & Johnston, 2012), Jordan (El-Mashaleh, 2007) have emphasized leadership (top management/CEOs) ineffectiveness as the major constrain to successful ICT adoption. Similarly, other studies (Martin & Hug, 2007;Ihua, 2009;Jung et al, 2003) have identified top management strategies toward managing employee behavioural change as another significant barrier to embracing technological change.…”
Section: Introductionmentioning
confidence: 99%
“…There have been efforts made to encourage students and lecturers in Universities in Africa to utilize Information Communication Technologies (ICTs) tools for research and teaching, nonetheless results usage is lacking (Danner & Pessu, 2013;Eze, Awa, Okoye, Emecheta & Anazodo, 2013;Ng'ambi, Brown, Bozalek, Gachago & Wood, 2016). This can be seen in few research outputs from universities in Africa as well as poor universities ranking when compared to universities in other parts of the world (Lages, Patt & Shepelyansky, 2016;Okorie, 2013).…”
Section: Introductionmentioning
confidence: 99%